Combatting workplace violence against nurses in Bangladesh - Silvia Ferdousi; Moustaq Karim Khan Rony (Belitung Raya Foundation, Indonesia, 2022)
This letter aims to respond to Tosepu et al. that workplace violence against nurses increases dramatically in developed and developing countries. This leads to a frustrating and unsustainable work environment. Furthermore, workplace violence has the potential to have long-term physical and psychological implications for all employees and a detrimental effect on the general morale of a healthcare organization. In this letter, we add the evidence of the workplace violence against nurses in Bangladesh, which contributes to increased health job discontent, decreased employee engagement, excessive absenteeism from work, a strong desire to resign, low medical safety ratings, and a high frequency of adverse clinical outcomes. In addition, people who live in hill communities and waterlogged areas do not have access to health care privileges due to workplace violence against nurses. Efforts to combat workplace violence against nurses are therefore very much needed.